Impact of Staff Remuneration on the Performance of Journalists in Osun State (Journal of Management and Social Sciences, 2023)
The study examined the impact of remuneration on the performance of journalists using selected journalists from media houses in Osun State. The paper adopted a survey method. It was guided by Social Theory of Journalism developed by Dennis McQuail, and Equity Theory propounded by John Adam. Findings revealed that journalists in Osun State were poorly remunerated. It was discovered that better pay for journalists will lead to better performance as the remuneration received is directly linked to the performance of journalists. Findings also showed that prevailing wage rate and ability of organisations to pay are the key factors that are responsible for the payment of remuneration of journalists in the state, which affects journalist’s editorial decision and ability to uphold the ethics of journalism leading to taking gratifications. The study recommended that media establishments should work out different types of remunerations. Other benefits for the staff (both cash and non-cash based) and should be paid as and when due. To upscale the performance of journalists, media organisations should ensure that journalists are well remunerated in order to carry out their functions satisfactorily. This paper concluded that remuneration impacts the performance of journalists in four ways out of six areas that were measured. It was equally concluded that staff remuneration affects the editorial independence of journalists and their ability to uphold the ethics of journalism. The study also concluded that remunerations and other benefits determine to a large extent, how journalists perform their professional functions and obey the guiding principles of their profession.